Erratum to rhinovirus is associated with severe adult community-acquired pneumonia in China - Wang, Keqiang; Xi, Wen; Yang, Donghong; Zheng, Yali; Zhang, Yaqiong; Chen, Yusheng; Yan, Chunliang; Tian, Guizhen; An, Shuchang; Li, Xiangxin; An, Fucheng; Du, Juan; et al. (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
Erratum to: J Thorac Dis 2017;9:4502-11